Characterizing convective heat transfer using infrared thermography and the heated-thin-foil technique - Stafford, J; Walsh, E; Egan, V (2009)
Convective heat transfer, due to axial flow fans impinging air onto a heated flat plate, is investigated with infrared thermography to assess the heated-thin-foil technique commonly used to quantify two-dimensional heat transfer performance. Flow conditions generating complex thermal profiles have been considered in the analysis to account for dominant sources of error in the technique. Uncertainties were obtained in the measured variables and the influences on the resultant heat transfer data are outlined. Correction methods to accurately account for secondary heat transfer mechanisms were developed and results show that as convective heat transfer coefficients and length scales decrease, the importance of accounting for errors increases. Combined with flow patterns that produce large temperature gradients, the influence of heat flow within the foil on the resultant heat transfer becomes significant. Substantial errors in the heat transfer coefficient are apparent by neglecting corrections to the measured data for the cases examined. Methods to account for these errors are presented here, and demonstrated to result in an accurate measurement of the local heat transfer map on the surface. © 2009 IOP Publishing Ltd.